An MILP approach for the optimal design of renewable battery-hydrogen energy systems for off-grid insular communities. (1st October 2021) - Marocco, Paolo; Ferrero, Domenico; Martelli, Emanuele; Santarelli, Massimo; Lanzini, Andrea
Highlights: Optimal design of off-grid hydrogen-battery energy systems by means of MILP. Wear costs of batteries and H2 -based devices are considered. Hydrogen is required as longer-term storage to achieve energy independence. Demand response program mainly affects the battery capacity. Abstract: The optimal sizing of stand-alone renewable H2 -based microgrids requires the load demand to be reliably satisfied by means of local renewable energy supported by a hybrid battery/hydrogen storage unit, while minimizing the system costs. However, this task is challenging because of the high number of components that have to be installed and operated. In this work, an MILP optimization framework has been developed and applied to the off-grid village of Ginostra (on the Stromboli island, Italy), which is a good example of several other insular sites throughout the Mediterranean area. A year-long time horizon was considered to model the seasonal storage, which is necessary for off-grid areas that wish to achieve energy independence by relying on local renewable sources. The degradation costs of batteries and H2 -based devices were included in the objective function of the optimization problem, i.e., the annual cost of the system. Efficiency and investment cost curves were considered for the electrolyzer and fuel cell components in order to obtain a more detailed and precise techno-economic estimation. The design optimization was also performed with the inclusion of a general demand response program (DRP) to assess its impact on the sizing results. Moreover, the effectiveness of the proposed MILP-based method was tested by comparing it with a more traditional approach, based on a metaheuristic algorithm for the optimal sizing complemented with ruled-based strategies for the system operation. Thanks to its longer-term storage capability, hydrogen is required for the optimal system configuration in order to reach energy self-sufficiency. Finally, considering the possibility of load deferral, the electricity generation cost can be reduced to an extent that depends on the amount of load that is allowed to participate in the DRP scheme. This cost reduction is mainly due to the decreased capacity of the battery storage system.